A novel mutation in ALS2 associated with severe and progressive infantile onset of spastic paralysis. (3rd April 2017) - Tariq, Huma; Mukhtar, Shahid; Naz, Sadaf
Abstract: Infantile onset ascending spastic paralysis (IAHSP) is a type of recessively inherited spastic paraplegia. We investigated the clinical and genetic cause of a recessively inherited disorder in two siblings manifesting severe spasticity in the lower limbs which hindered their gait. A novel homozygous nonsense mutation c.1918 C > T (p.Arg640*) was identified after whole-exome sequencing within ALS2 in the DNA of both patients. The obligate carriers were heterozygous for the mutation and other unaffected members were homozygous for the wild type allele. The variant was absent from 100 control chromosomes and all public databases. This report extends the allelic heterogeneity of ALS2 mutations and emphasizes the importance of genetic testing for diagnosis of pediatric disorders.